Досвід роботи вітчизняних підприємств в умовах карантинних обмежень: соціально-трудові аспекти - Хандій, О.О.; Шамілева, Л.Л. (Вісник економічної науки України, 2020)
У статті досліджено досвід роботи вітчизняних підприємств в умовах карантинних обмежень, проаналізовано найбільш поширені кадрові рішення під час карантину, серед яких переведення на часткову зайнятість, дистанційну роботу, відправлення у відпустку, звільнення працівників, та їх вплив на національний ринок праці. Виявлено основні негативні тенденції в системі соціально-трудових відносин внаслідок економічної рецесії та карантинних обмежень соціально-економічної діяльності під час пандемії Covid-19. Визначено обсяги та рівні офіційного й прихованого безробіття, наведено їх порівняльний аналіз за статистичними даними й результатами соціологічних опитувань. Розраховано втрати робочого часу за другий квартал 2020 р., як результат впровадження жорстких карантинних обмежень. Визначено дисбаланс між попитом та пропозицією робочої сили, зміни настроїв і поведінки учасників на ринку праці, які виступають індикатором кризових процесів у сфері зайнятості. Досліджено зниження доходів працюючого населення, зміну їх структури внаслідок зменшення оплати праці при падінні обсягів реалізації та доходів підприємств. В статье исследован опыт работы отечественных предприятий в условиях карантинных ограничений, проанализированы наиболее распространенные кадровые решения и их влияние на национальный рынок труда. Выявлены основные негативные тенденции в системе социально-трудовых отношений как результат влияния экономического спада и государственных мер по ограничению социально-экономической деятельности субъектов рынка во время пандемии Covid-19. Определены объемы и уровни официальной и скрытой безработицы, проведен их сравнительный анализ на основе статистических данных и результатов социологических опросов. Рассчитаны потери рабочего времени за второй квартал 2020 г., как результат внедрения жестких карантинных ограничений. Определены дисбаланс между спросом и предложением рабочей силы, изменения настроений и поведения участников на рынке труда, которые являются индикатором кризисных процессов в сфере занятости. Исследовано снижение доходов работающего населения и их структуры вследствие уменьшения оплаты труда при падении объемов реализации и доходов предприятий. The system of social and labor relations proved to be the most vulnerable to the impact of the financial and economic crisis and the Covid-19 coronavirus pandemic, and most of all suffered from measures aimed at overcoming the spread of coronavirus disease. The experience of domestic enterprises in the conditions of quarantine restrictions was investigated in the article. The most common personnel decisions during quarantine, including transfer to part-time employment, remote work, vacation, dismissal, were analyzed. Their impact on the national labor market was analyzed. The main negative trends in the system of social and labor relations due to the economic recession and quarantine restrictions on economic activity during the Covid-19 pandemic were identified. The volumes and levels of official and hidden unemployment were determined, their comparative analysis was carried out on the basis of statistical data and the results of sociological surveys. The uneven nature of hidden unemployment by type of economic activity was determined. The loss of working time for the second quarter of 2020 as a result of the introduction of strict quarantine restrictions was calculated. The imbalance between labor supply and demand, changes in attitudes and behavior of participants in the labor market, which act as an indicator of crisis processes in the field of employment, were characterized. The reasons for the decline in job search indices, declining labor supply, imbalance and weak labor market flexibility in the short term have been identified. The main trends and patterns of the labor market, changes in employers' requirements for job applicants were described. The decline in incomes of the working population, the change in their structure due to the reduction of wages in the fall of sales and income of enterprises was studied. It is emphasized that the methodology of data collection by the State Statistics Service and the State Employment Service does not provide the opportunity to obtain complete operational information and under these conditions for rapid assessment and analysis of the situation it is necessary to use additional information from state and non-state online resources, sociological surveys and others sources.